Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus - Trýzna, Miloš (Zootaxa, 2017)
A new species Tophoderes banari Trýzna sp. nov. (Anthribidae: Anthribinae: Tophoderini) from east Madagascar is described. Both sexes and male and female genitalia are illustrated. Colour photographs of all Madagascan species of the genus Tophoderes are added.